PENGARUH MOTIVASI, BIAYA PENDIDIKAN, dan PENGETAHUAN TENTANG AKUNTAN PUBLIK (AP) TERHADAP MINAT MAHASISWA AKUNTANSI MENGIKUTI PPAk - Amiroh Alfi Hasanah; Andri Waskita (Fakultas Ekonomi UNIBBA, 2021)
The purpose of this study was to examine the influence of motivation, cost of education, and knowledge of public accountants on the interest of accounting students to attend accounting profession education. This research method uses quantitative methods and primary data which is distributed via google from. The population used in this study were accounting students of class 2017 and 2018 at Sarjanawiyata Tamansisawa University. The sampling technique used the snowball sampling technique. The data analysis technique used in this study is multiple linear analysis techniques.The results of the study stated that career motivation, quality motivation, and knowledge of public accountants had a positive effect on the interest of accounting students in participating in PPAk. Economic motivation has a negative effect on the interest of accounting students to follow PPAk. while the cost of education has no effect on the interest of accounting students to attend PPAk.